Hydrothermal synthesis of Zn-Mg-based layered double hydroxide coatings for the corrosion protection of copper in chloride and hydroxide media - Nikhil; Ji G.; Prakash R. (My University, 2025)
Layered double hydroxides (LDHs) hinder corrosive elements by forming a double layer and locking them between its layers. Hence, LDHs are interesting materials in corrosion inhibition. In this work, Zn-Mg-based LDHs are grown over a copper substrate by using a hydrothermal method. Two types of Zn-Mg-based LDH coating are prepared based on hydrothermal reaction time. Both types are characterized through Fourier transform infrared spectroscopy, Raman spectroscopy, high-resolution scanning electron microscopy, energy dispersive X-ray analysis, atomic force microscopy, and X-ray diffraction. Results show that the two types of LDH coating are successfully grown on copper; however, they differ in thickness and structural configuration. Corrosion testing of the LDH coatings is executed in 0.1 M NaCl and 0.1 M NaOH through alternating current impedance measurements and Tafel polarization curves. Results show that L48 gives more than 90% protection to copper, which is higher than the protection provided by L24. However, both LDH coatings (L24 and L48) are more effective corrosion inhibitors in NaCl than in NaOH, suggesting that the LDH coatings can more efficiently exchange Cl ions than OH ions. © 2021, University of Science and Technology Beijing.